The Effect of Open-Ended Problem Based Learning Model on Energy Sources Material on Critical Thinking Skills and Pro-Environmental Attitudes of Elementary School Teacher Education Students - Damayanti*, Ika; Purwanti, Siwi; Hastuti, Woro Sri; Nugroho, Ikhlasul Ardi; Supartinah, Supartinah; Andania, Ruqoyyah Amilia; Luhanarky, Ayu (Universitas Syiah Kuala, 2025)
Critical thinking is one of the skills that need to be mastered in the 21st century. CTS especially in prospective elementary school teacher students, need to be developed because as an educator, teachers must face all the problems encountered in the learning process. This study aims (1) to determine whether there is a difference in CTS among students before and after receiving treatment (2) to identify the categories of differences in CTS among students after receiving treatment and its impact on their pro-environmental attitudes. This study is a pre-experimental research using a one group pretest posttest design. Students of the Elementary Education Study Program at Ahmad Dahlan University were given treatment through PBL by conducting an experiment on the use of banana peel waste as a substitute for carbon powder in batteries. A pretest was given before the students received treatment and the lecturer conducted the learning by presenting environmental problems, followed by a posttest. Data were analyzed using SPSS version 24 software to determine differences based on the Hake factor or N-gain. Additionally, the researcher analyzed the data using a paired t-test to assess the effectiveness of the PBL model. Based on the results of the study conducted using the N-Gain test, the average value obtained was 0.7239. This indicates that students experienced a significant improvement in learning outcomes, categorized as high (g 0.7). Furthermore, based on the results of observations and interviews, there was a significant impact after students participated in learning with treatment on the material of energy sources affecting the environment. Students demonstrated a positive attitude toward the environment, as evidenced by their sensitivity and openness to contributing to environmental conservation. Based on the gain values obtained, it can be concluded that the PBL model influences students' CTS and supports a positive attitude toward the environment